Attention, Interest, Search, Action, and Share Method as a Sales Promotion Strategy for Indonesian Public Figure Food Products through Creative Advertising - DI Aryani; RH Mulyadi; H Setiawan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to examine and analyze the phenomena of Indonesian public figures' food businesses in terms of creative advertising using the Attention, Interest, Search, Action, and Share (AISAS) technique, as well as its relationship to Integrated Marketing Communication (IMC). The research method is qualitative, using a case study approach, and it entails gathering thorough data from a variety of sources connected to the study's subject. The findings suggest that the AISAS approach via IMC is a product marketing tool that can spark innovative digital sales concepts. According to research, prominent figures' popularity does not ensure the long-term marketing of a product because it is merely a short-term sales plan that does not consider long-term programs. This study's impact is likely to be significant